Transvenous embolization of dural fistulas involving the transverse and sigmoid sinuses. - Halbach, V V; Higashida, R T; Hieshima, G B; Mehringer, C M; Hardin, C W (American Journal of Neuroradiology, 1989)
Eleven patients with dural fistulas involving the transverse and sigmoid sinuses were treated by transvenous embolization with coils or liquid adhesives. Seven patients underwent preoperative embolization of the external supply followed by direct surgical exposure of the sinus: liquid adhesives were used in four patients and coils in the remaining three. Four of these patients had complete obliteration of their fistulas and there was 95% reduction in the remaining three. Four patients had transvenous placement of coils from a transfemoral approach. In three, the ipsilateral sigmoid sinus was thrombosed and a contralateral approach across the torcular herophili was used. Coils were used in all four patients; one patient also had liquid adhesives placed within the sinus. Complete cure was achieved in one patient, 95% reduction in another, and 50% and 40%, reductions in the remaining two. Two transient complications occurred, one related to venous occlusion secondary to liquid adhesives and another related to transient occlusion of the vestibular aqueduct. Obliteration of dural fistulas involving the transverse and sigmoid sinuses can be achieved by placement of embolic material within the involved sinus from a transvenous approach; both coils and liquid adhesives can achieve this goal.